Plexiform schwannoma of the finger: A case report and literature review - Nafiseh Mortazavi; Kambiz Novin; Farahnaz Bidari Zerehpoosh; Managol Sadatsafavi (Wolters Kluwer Medknow Publications, 2017)
A 49-year-old woman with a long history of a subcutaneous mass on the dorsal side of her 4th finger of the right hand visited a dermatologist because of slight enlargement of the mass. Her past medical history was notable only for a mitral valvuloplasty performed 20 years earlier. Physical examination revealed a small, round, firm subcutaneous mass on the dorsal side of her proximal interphalangeal joint of the right 4th finger. The mass was immobile and nontender and its overlying skin was intact. An excisional biopsy was done for the patient and the specimen was sent for pathologic evaluation. On microscopic examination, the final diagnosis of plexiform schwannoma was made for the lesion. The aim of this publication is to report a rare case of plexiform schwannoma of the soft tissue and a literature review to provide a better understanding about its characteristics including epidemiologic factors and pathologic evaluation.